Число двойных перегибов как индикатор степени старения кабельных бумаг - Беспрозванных, А.В.; Москвитин, Е.С. (Електротехніка і електромеханіка, 2011)
During power cables operation, degradation of paper isolation mechanical characteristics is observed. The statistical distribution density curve for the double-kink number of non-aged cables is non-symmetric and bimodal. It results from the discrete structure of cable isolation volume and corresponds to levels of mechanical durability (resource). For ageing cables, durability levels are degenerated. Variation diagrams of the double-kink number of cable wrapping display a break which corresponds to the critical level of mechanical durability. Critical levels for the double-kink number of paper isolation of 1-10 kV power cables are specified.